Effect of wavy amplitude on the thermo-hydraulic performance of a single-walled wavy microchannel - Toh, Benjamin Jun Jie (2018)
Microchannel heat transfer has proven to have superior heat transfer capabilities as compared to conventional channels. A microchannel with annular gap of 300 μm was fabricated using an insert of 19.4 mm which is concentrically fitted into a hollow cylinder of 20 mm. Sinusoidal waves profiles on the inserts were used to increase the heat transfer capabilities by using single-phase state distilled water as the working fluid. Two different profiles on insert with wave amplitudes at three different wavelengths were tested. The thermal and hydrodynamic performance of six different inserts were studied in comparison to the plain insert. Eleven experimental data points were collected per wavy insert, with a flow rate ranging from 2.00 to 6.00 L/min at an interval of 0.5 L/min in a randomized sequence. A power input of 1000W was supplied in the study. The wavy profile has a significant improvement in Nusselt number of 205 % at a Reynolds number of 3314, recorded by test specimen with wave amplitude of 125 mm and wavelength of 3 mm. The study also shows that insert profiles with higher wave amplitudes give a higher Nusselt number for a given Reynolds number. However, for these cases, a higher Darcy friction factor and hence higher pressure occurred. Under the same operating condition, the wavy profile is able to remove 53% more heat as compared to plain insert at an equal pumping power, which is recorded by inserts with wave amplitude of 10 mm and wavelength of 3 mm and 6 mm at Reynolds number of 2672 and 2992 respectively.